Effect of the Knee and Hip Angles on Knee Extensor Torque: Neural, Architectural, and Mechanical Considerations - Garnier, Yoann M.; Lepers, Romuald; Canepa, Patrizio; Martin, Alain; Paizis, Christos (Frontiers in Physiology, 2022)
This study examined the influence of knee extensors’ hip and knee angle on force production capacity and their neuromuscular and architectural consequences. Sixteen healthy men performed sub-maximal and maximal voluntary isometric contractions (MVIC) of knee extensors with four different combinations of the knee and hip angles. Muscle architecture, excitation-contraction coupling process, muscular activity, and corticospinal excitability were evaluated on the vastus lateralis (VL) and rectus femoris (RF) muscles. MVIC and evoked peak twitch (Pt) torques of knee extensors increased significantly (p < 0.05) by 42 ± 12% and 47 ± 16% on average, respectively, under knee flexed positions (110° flexion, 0° = full extension) compared to knee extended positions (20° flexion) but were not different between hip positions (i.e., 0° or 60° flexion). Knee flexion also affected VL and RF muscle and fascicle lengths toward greater length than under knee extended position, while pennation angle decreased for both muscles with knee flexion. Pennation angles of the VL muscle were also lower under extended hip positions. Alternatively, no change in maximal muscle activation or corticospinal activity occurred for the VL and RF muscles across the different positions. Altogether these findings evidenced that MVIC torque of knee extensors depended particularly upon peripheral contractile elements, such as VL and RF muscle and fascicle lengths, but was unaffected by central factors (i.e., muscle activation). Furthermore, the hip position can affect the pennation angle of the VL, while VL muscle length can affect the pennation angle of the RF muscle. These elements suggest that the VL and RF muscles exert a mutual influence on their architecture, probably related to the rectus-vastus aponeurosis.